High Accuracy Evaluation of the EFIE Matrix Entries on a Planar Patch - Bibby, Malcolm M.; Peterson, Andrew F. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A method for the evaluation of the integral of the free-space Green’s function on a planar patch, that is exact to machine precision, is developed. The results are used to evaluate two other, commonly used, methods - singularity extraction and singularity cancellation. It was found that these two methods produced unacceptable results. It is shown what steps need to be taken to improve the performance of these methods for patches with varying aspect ratios.